Data Jenis-jenis Kupu-kupu Di Lingkungan Perumahan Bukit Kalibagor - Rahmawati, Fitri; Prakoso, Bagas (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2021)
Butterflies are part of the biological wealth that must be preserved. Butterflies have important values ??for humans and the environment, including: ecological, aesthetic, educational, endemic, conservation and cultural values. Butterflies are one type of insect that comes from the order Lepidotera, namely insects whose wings are covered by scales, and have a very important role in maintaining the ecosystem. Good geographical distribution and diversity of butterflies can provide good information in environmental studies as environmental indicators, as well as changes that may occur. Butterflies also make a very significant contribution in maintaining the balance of nature by acting as pollinators in flowers along with other pollinating animals. Butterflies are also insects whose existence is determined by their distributional ability and adaptation to environmental factors. Factors that play an important role in the existence of butterflies are plants. Plants are used by butterflies as host plants and food sources. Butterfly diversity is also influenced by abiotic factors. Several abiotic factors that affect the life of butterflies, among others: temperature, humidity, season, and wind speed. How the types of butterflies in the residential area of ??Bukit Kalibagor Indah have never been studied and published considering that currently the types of butterflies in each ecosystem have different species. This study aims to determine the types of butterflies in the Bukit Kalibagor Indah residential area. The parameters observed were the types of butterflies. Samples were taken from the Bukit Kalibagor Indah residential area. The research was conducted in April 2021 - June 2021 for 2 months. This research was conducted using the roaming method. The results of the study found 10 species with 6 genera from 48 individuals belonging to 2 families, namely Nympalidae (3 species) and Pieridae (7 species). Keywords: Types, Butterflies, Beautiful Kalibagor Hill Housing